Evidence-based teaching : a practical approach - Petty, Geoffrey, ....- (Cheltenham : Nelson Thornes, 2009)
Completely revised, this edition with its fresh new design, teaching strategies, ideas and advice provide general principles for teaching. A Coherent, evidence based view of teaching and learning, presenting some radical new methods known to greatly improve student achievement.
1: What is evidence-based teaching? 2: What methods work best 3: The top teaching methods 4: Seven principles for evidence-based teaching 5: Choosing and using teaching methods 6: Teaching intelligence 7: What do the best teachers, schools and colleges do? 8: Your own evidence 9: The rational curriculum 10: Management and leadership
Previous ed.: 2006.
Includes bibliographical references and index.
Keywords: Didactiek; Effective teaching -- Great Britain